2011
DOI: 10.1021/jf103811g
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Potential of Fungal and Plant Laccases for Active-Packaging Applications

Abstract: Laccases from Trametes versicolor (TvL), Myceliophthora thermophila (MtL), and Rhus vernicifera (RvL) were investigated with regard to their potential utilization as oxygen scavengers in active packages containing food susceptible to oxidation reactions. The substrate selectivity of the laccases was investigated with a set of 17 reducing substrates, mainly phenolic compounds. The temperature dependence of reactions performed at low temperatures (4-31 °C) was studied. Furthermore, the laccases were subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Oxygen scavengers like eosin, palladium, and laccases are used for controlling the residual oxygen levels that can make a difference to off-flavor development, color changes, nutrition losses as well as microbial growth in packaged foods. 61,122,123 Cherpinski et al electrospun the poly(3-hydroxybutyrate) (PHB) oxygen scavenging films containing palladium nanoparticles. They found that the presence of palladium nanoparticles enhanced the barrier property of PHB films against water and oxygen.…”
Section: ■ Electrospinning Of Pla Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen scavengers like eosin, palladium, and laccases are used for controlling the residual oxygen levels that can make a difference to off-flavor development, color changes, nutrition losses as well as microbial growth in packaged foods. 61,122,123 Cherpinski et al electrospun the poly(3-hydroxybutyrate) (PHB) oxygen scavenging films containing palladium nanoparticles. They found that the presence of palladium nanoparticles enhanced the barrier property of PHB films against water and oxygen.…”
Section: ■ Electrospinning Of Pla Nanofibersmentioning
confidence: 99%
“…Besides antimicrobial and antioxidant agents, other types of active agents including oxygen scavengers, carbon dioxide emitters, and ethylene scavengers have been used to preserve the quality and extend the shelf life of foodstuff as well. Oxygen scavengers like eosin, palladium, and laccases are used for controlling the residual oxygen levels that can make a difference to off-flavor development, color changes, nutrition losses as well as microbial growth in packaged foods. ,, Cherpinski et al electrospun the poly­(3-hydroxybutyrate) (PHB) oxygen scavenging films containing palladium nanoparticles. They found that the presence of palladium nanoparticles enhanced the barrier property of PHB films against water and oxygen .…”
Section: Applictions Of Pla-based Nanofibers For Food Packagingmentioning
confidence: 99%
“…Laccase is a polyphenol oxidase containing copper ions, soluble in urushiol. Although the total content of laccase in raw lacquer is very low, their role is particularly important [18][19][20][21][22][23][24]. In the drying process of raw paint, the copper ions in laccase catalyze the drying of paint films by transferring electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on laccase and oxygen scavenging for active packaging has focused on small phenolic compounds [ 21 ], and on the possibility to use polymeric substances such as lignosulfonates and other technical lignin preparations including Kraft lignin, organosolv lignin, and hydrolysis lignin [ 7 , 16 ]. However, there are no studies to date on how the properties of a certain type of lignin derivative affect the reaction.…”
Section: Introductionmentioning
confidence: 99%